The impact of the current 4cs skills gap in organizations: Using emotional intelligence to develop competencies - Bakhshandeh, Behnam (London Routledge, 2025)
The shortage of skills in the workforce is one of the major problems facing enterprises today.This book explores the impact of the 21st-century 4Cs skills gap in organizations and how it affects their performance, innovation, and competitiveness.